Cabo Verdean rhythms: kolá san jon, spatialization, and the performance of creolidade - Ringsmut, Martin 19XX- (SOAS studies in music, 2025)
"Cabo Verdean Rhythms examines the rhythms, movements and performances of Kolá San Jon, a performative tradition central to Cabo Verde's festas juninas, as a lens for understanding the ongoing negotiations of social and cultural boundaries in Cabo Verde. The book examines Kolá San Jon as a site of spatialization and creolization, processes that are closely linked to the colonial and post-colonial histories of the archipelago. Beginning with an examination of the concept of Creolidade as a dynamic and contested process, the book goes on to trace the historical connections between the islands of São Vicente and Santo Antão, exploring how these inter-island relationships have shaped the Kolá San Jon tradition. It analyzes the construction of identity and a sense of belonging through drumming and dance, and considers processional performances as key moments of spatial and social organization. Through the concept of ritual failure, the book reflects on the fragility and contested nature of these practices. Bringing together the interdisciplinary fields of ethnomusicology, postcolonialism and spatial politics, Cabo Verdean Rhythms offers novel perspectives for understanding the nexus of sound, space, and identity which will be of interest to both researchers and postgraduate students"-- Provided by publisher